2020
DOI: 10.1111/jfbc.13573
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf attenuates atherosclerotic lesions in patients with coronary heart disease possibly via 1‐Deoxynojirimycin: A placebo‐controlled, double‐blind clinical trial

Abstract: Coronary heart disease (CHD) refers to coronary atherosclerosis, which causes vascular stenosis or obstruction. Because of its high mortality and disability rate, it seriously endangers human life (Lee et al., 2018; Zannad et al., 2018). A large number of clinical research data show that the risk factors are associated with CHD development, including blood pressure (BP), lipid disorders, abnormal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…An increase in ROS on exposure to cigarette smoke and a high‐fat diet was observed (Lee, Lee, et al, 2019; Suryadinata & Wirjatmadi, 2021). Contrastingly, mulberry polyphenol, 1‐DNJ improved the antioxidant enzymes in coronary heart patients (Y. Wang et al, 2021). A significant decline in lipotoxicity via moderating the ROS production, GSH‐Px content, and mitochondrial dysfunction after treatment with mulberry digest (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in ROS on exposure to cigarette smoke and a high‐fat diet was observed (Lee, Lee, et al, 2019; Suryadinata & Wirjatmadi, 2021). Contrastingly, mulberry polyphenol, 1‐DNJ improved the antioxidant enzymes in coronary heart patients (Y. Wang et al, 2021). A significant decline in lipotoxicity via moderating the ROS production, GSH‐Px content, and mitochondrial dysfunction after treatment with mulberry digest (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin‐rich mulberry leaf jelly improves the serum lipid profile in dyslipidemic subjects (On‐Nom et al, 2020). In vivo administration of 1‐DNJ effectively reduces the lipid profile, inflammation, and carotid intima‐media thickness in coronary heart patients (Wang et al, 2021). Furthermore, upregulation of genes involved in bile acid and hepatic synthesis (Lee, Lee, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that high-dose 1-deoxynojirimycin (1-DNJ), which is found to be distributed among the mulberry species, reduces aspartate transferase (AST) and alanine transferase (ALT) levels, and increases sensitivity to fat in high-fat mice [ 12 , 13 ]. The 1-DNJ significantly reduces intestinal glucose absorption [ 14 ], improves the serum lipid profile in coronary heart disease [ 15 ], inhibits metastasis of melanoma cells [ 16 ], and improves insulin sensitivity [ 17 ]. In addition, the effects of mulberry leaf on both humoral and cellular immunity have been proven by increasing antibody production levels during in vitro and in vivo experiments [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaf tea and it major ingredient deoxynojirimycin significantly repressed cerebrovascular and cardiovascular events and reduced carotid intima-media thickness in patients with coronary heart disease in a clinical trial [14]. The polyphenol contents of mulberry are very similar to those of mulberry leaf, thereby suggesting that mulberry polyphenols (MPE) may also play a role in anti-atherosclerosis treatment [15].…”
Section: Introductionmentioning
confidence: 99%